Effect of Terminalia Chebula (Haritaki) on Serum Aspartate Aminotransferase, Alanine Aminotransferase in Paracetemol induced liver damage in Wister Albino Rats - Yeasmin, Tania; Akhter, Qazi Shamima; Siddika, Syeda Tasfia; Karim, Fayeza (Journal of Bangladesh Society of Physiologist, 2015)
Background: Liver plays a major role in detoxification and excretion of many endogenous and exogenous compounds. Any injury may lead to severe liver damage and impairment of liver function. Harbal plants such as Terminalia chebula (Haritaki) may have free radical scavenging activity thereby can be used for the prevention and treatment of liver damage. Objective: To observe the effect of Terminalia chebula on paracetamol induced changes of serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT) in Wister albino rats. Methods: This experimental study was carried out in the Department of Physiology, Dhaka Medical College, Dhaka from January to December 2013. Total 44 rats with age 90 to 120 days, weighing between 150 to 200 gm were selected. After acclimatization for 14 days, they were divided into base line control (BC, n=11), paracetamol treated control (PC, n=11),Terminalia chebula pretreated and paracetamol treated (TCP-PCT n=11) and paracetamol pretreated and Terminalia chebula treated group (PCP-TCT, n=11). All groups received basal diet for 21 consecutive days. In addition to basal diet, rats of BC received propylene glycol (2ml/kg body weight, orally) and PC received single dose of paracetamol suspension (750mg/kg body weight, orally) on 21st day. Rats of TCP-PCT received Terminalia chebula extract (200 mg/kg body weight, orally) for 21 consecutive days and paracetamol suspension (750mg/kg body weight, orally) on 21st day. Again, rats of PCP-TCT received paracetamol suspension (750mg/kg body weight, orally) on the 1st day and Terminalia chebula extract (200 mg/kg body weight orally) for 21 consecutive days. All rats were sacrificed on 22nd day and then blood samples were collected. For assessment of liver function serum AST and ALT levels were estimated by using standard laboratory kits. The statistical analysis was done by one way ANOVA and post hoc Bonferroni test as applicable. Results: The mean serum AST and ALT levels were significantly (p<0.001) higher in PC in comparison to those of BC. Serum AST and ALT levels of all experimental groups were significantly (P<0.001) lower than PC group. Conclusion: From the results of this study, it may be concluded that Terminalia chebula may have some hepatoprotective effects in paracetamol induced liver damage in rats. Bangladesh Soc Physiol. 2015, June; 10(1): 1-5